2016
DOI: 10.1515/raon-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of weight loss to planning target volume significantly impacts setup errors in nasopharyngeal cancer patients undergoing helical tomotherapy with daily megavoltage computed tomography

Abstract: BackgroundChanges in head and neck anatomy during radiation therapy (RT) produce setup uncertainties of nasopharyngeal cancer (NPC) irradiation. We retrospectively analyzed image guidance data to identify clinical predictors of setup errors.Patients and methodsThe data of 217 NPC patients undergoing definitive RT on a helical tomotherapy (HT) unit were analyzed. Factors including tumor stage, body mass index, weight loss, and planning target volume (PTV) were assessed as predictors of daily megavoltage compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…All three cases received chemotherapy in addition to radiotherapy (2 had cisplatin 100 mg/m 2 and 1 had carboplatin with previous induction chemotherapy). The mean fraction for rescan CT was 21 (range, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. No other primaries were found to be correlated with need for ART ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three cases received chemotherapy in addition to radiotherapy (2 had cisplatin 100 mg/m 2 and 1 had carboplatin with previous induction chemotherapy). The mean fraction for rescan CT was 21 (range, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. No other primaries were found to be correlated with need for ART ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The literature provides contradictory data about the correlation of weight loss and the necessity for ART. Wei-Hsien Hou et al found that NPC patients with weight loss > 5% and smaller PTVs were more likely to have increased setup errors (28). Mahmoud et al found weight loss of more than 9.6% as the critical value to trigger ART in terms of target under dosing and/or spinal cord/parotids overdosing (29).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that weight loss affects interfractional set up errors 34,35 , but there is no report on intrafractional movement. The association between weight loss and intrafractional movement in our study can be discussed in terms of the following two aspects: rst, due to toxicity or nausea induced by a high radiation dose during RT, the patient's appetite deteriorates, leading to a poor condition; therefore, the weight decreases with progression of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The correlations between ΔBW and Δ(inter) were significant in several studies [23,24], although some studies reported contrasting results [25,26]. Hou et al [23] reported that patients with nasopharyngeal cancer with weight loss of >5% had significantly larger ΔAP(inter). Zia et al [24] found that weight loss was associated with ΔLR(inter).…”
Section: Discussionmentioning
confidence: 99%